Oxford Energy Forum, Issue 100 - Bassam Fattouh; Laura El-Katiri (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2015)
This special issue of the Forum is dedicated to Robert Mabro who founded the Oxford Energy Policy Club in 1976, the Oxford Energy Seminar in 1979, and the Oxford Institute for Energy Studies in 1982.
Keywords: 330